Pendampingan Masyarakat Sub Urban Melalui Penguatan Kapasitas Sumber Daya Manusia di Kelurahan Pesantren Kecamatan Mijen Kota Semarang - Awaludin Pimay; Agus Riyadi; Nur Hamid (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
The development of technology and information greatly affects sosial changes in the sosial order. One of them is a sub-urban community which is often interpreted as a transitional area. The purpose of this study was to find out how to assist sub-urban communities through strengthening the capacity of human resources in the Pesantren village, Mijen sub-district, Semarang city. This type of research is descriptive qualitative research. Data collection techniques through observation, interviews and documentation. The results of the study show, first, that there is a change and the creation of habituation in the work pattern of the fostered subjects that prioritizes the concept of hard and smart work. Second, the birth of community awareness in having a set of knowledge and skills (life skills) to increase religious knowledge in the community, and third the birth of assisted groups as teamwork that has high awareness and enthusiasm, and has the same ideals to build an assembly taklim.